2014
DOI: 10.1063/1.4894809
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Phase diagram of C36 by atomistic molecular dynamics and thermodynamic integration through coexistence regions

Abstract: We report an atomistic molecular dynamics determination of the phase diagram of a rigid-cage model of C36. We first show that free energies obtained via thermodynamic integrations along isotherms displaying “van der Waals loops,” are fully reproduced by those obtained via isothermal-isochoric integration encompassing only stable states. We find that a similar result also holds for isochoric paths crossing van der Waals regions of the isotherms, and for integrations extending to rather high densities where liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A cheap way to work out the entire phase diagram of a model fluid is by following the isothermal evolution of the pressure P as a function of density ρ, any loop in P (ρ) being the hallmark of the crossing of a two-phase region (see for instance Ref. [8,33,34]). However, traditional simulation methods usually fail to attain thermal equilibrium near transition points and the question is whether it is possible to obtain accurate transition thresholds from an equation of state which is only approximate in the coexistence regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cheap way to work out the entire phase diagram of a model fluid is by following the isothermal evolution of the pressure P as a function of density ρ, any loop in P (ρ) being the hallmark of the crossing of a two-phase region (see for instance Ref. [8,33,34]). However, traditional simulation methods usually fail to attain thermal equilibrium near transition points and the question is whether it is possible to obtain accurate transition thresholds from an equation of state which is only approximate in the coexistence regions.…”
Section: Discussionmentioning
confidence: 99%
“…[8,33,34]). However, traditional simulation methods usually fail to attain thermal equilibrium near transition points and the question is whether it is possible to obtain accurate transition thresholds from an equation of state which is only approximate in the coexistence regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the first inversion of concavity encountered corresponds to the first occurrence of liquid-vapor separation. We have recently showed that, despite their fake character, one can take advantage of these pressure loops to extract, by plain thermodynamic integration, the right liquid-vapor coexistence parameters [3,4].…”
Section: Introductionmentioning
confidence: 99%